2018
DOI: 10.1155/2018/8421979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Qufengtongluo Decoction on PI3K/Akt Signaling Pathway in the Kidney of Type 2 Diabetes Mellitus Rat (GK Rat) with Diabetic Nephropathy

Abstract: Qufengtongluo (QFTL) decoction is an effective treatment for diabetic nephropathy (DN). However, the underlying molecular mechanism is still unclear. In this study, we try to investigate whether QFTL decoction acts via inhibiting PI3K/Akt signaling pathway. Twenty-four GK rats were randomly divided into 3 groups: blank group, sham-operated group, and QFTL group. After model establishment, rats in QFTL group were given QFTL decoction by gavage, while the rest were given pure water. During the 8-week interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Furthermore, our results revealed a significant upregulation of the PI3K/Akt/mTOR pathway in MTX-treated rats and this may be explained by what was reported about the capability TGF-β in activating the PI3K/Akt/mTOR pathway [37,38]. Several reports demonstrated the involvement of the PI3K/Akt signaling in the pathogenesis of chemotherapy induced-nephrotoxicity like doxorubicin [11], MTX [5], and cisplatin [39,40].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, our results revealed a significant upregulation of the PI3K/Akt/mTOR pathway in MTX-treated rats and this may be explained by what was reported about the capability TGF-β in activating the PI3K/Akt/mTOR pathway [37,38]. Several reports demonstrated the involvement of the PI3K/Akt signaling in the pathogenesis of chemotherapy induced-nephrotoxicity like doxorubicin [11], MTX [5], and cisplatin [39,40].…”
Section: Discussionsupporting
confidence: 75%
“…Controversial results were reported in the PI3K/Akt pathway in different experimental models of induced-kidney injury. Some researchers reported its activation in the injured kidney [37,38,39,41,42,43,44] while others reported its downregulation [5,45,46,47,48]. This may be explained by using different animal models, experimental conditions, duration, therapies, phosphorylation sites analyzed, and detection methods in addition to the early and late stages of renal diseases [11,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that high-, medium- and low-dose Dex significantly inhibited β2-MG and α1-MG levels in rat urine, indicating that Dex prevented and delayed early renal dysfunction in DM rats. Masson staining highlights deposition of immune complexes on the glomerulus, basement membrane, mesangial matrix, and collagen fibers, and is crucial for assessment of renal fibrotic lesions [13]. Our results showed that Dex significantly inhibited deposition of fibrous material in rat kidney tissue.…”
Section: Discussionmentioning
confidence: 72%
“…The PI3K/Akt signaling pathway and NF-κB also contribute to the regulation of podocyte function. For example, Akt kinase is activated by TGF-β in diabetic kidneys, 35 and the morphology and function of podocytes are maintained by nephrin, which involves PI3K. PI3K also controls the excretion of microalbuminuria in DN.…”
Section: Discussionmentioning
confidence: 99%